Aristolactams and further constituents from Aristolochia chamissonis - TSURUTA, Angélica Yucari [UNESP]; BOMM, Mauro Dionei [UNESP]; Lopes, Márcia Nasser [UNESP]; Lopes, Lucia Maria Xavier [UNESP] (Editora Unesp, 2002)
Isolou-se do extrato etanólico de galhos de Aristolochia chamissonis espatulenol, sitosterol, sitosterol-beta-D-glicosídeo, colavelool, 13-epi-2-oxo-colavelool, trans-N-p-coumaroiltiramina, alantoína, ácido aristolóquico I e aristolactama AII. As estruturas da aristolactama AII e da piperolactama A são revisadas com base em análises espectrométricas e derivatizações químicas.

From the ethanol extract of the stems of Aristolochia chamissonis, spathulenol, sitosterol, beta-sitosteryl-D-glucoside, kolavelool, 13-epi-2-oxo-kolavelool, trans-N-p-coumaroyltyramine, allantoin, aristolochic acid I, and aristolactam AII were isolated. The structures of aristolactam AII and piperolactam A have been revised by means of spectroscopic methods and chemical derivatizations.
Aristolactamas e Outros Constituintes Químicos de Aristolochia chamissonis
Keywords: Aristolochiaceae; Aristolochia chamissonis; diterpenos; trans-N-p-coumaroiltiramina; alantoína; aristolactama AII; piperolactama A; Aristolochiaceae; Aristolochia chamissonis; diterpenes; trans-N-p-coumaroyltyramine; allantoin; aristolactam AII; piperolactam A